Combination of cisplatin and ethyl acetate extract of Vernonia amygdalina Delile induces cell cycle arrest and apoptosis on PANC-1 cells via PI3K/mTOR - Poppy Anjelisa Zaitun Hasibuan; Jane Melita Keliat; Muhammad Fauzan Lubis (GarVal Editorial Ltda., 2024)
Context: Vernonia amygdalina Delile (VAD) is known as a potential plant with a wide variety of medicinal properties, including anticancer. Aims: To evaluate the combination effect of VAD extract with cisplatin (CIS) against PANC-1 cells, focusing on cell cycle arrest and apoptosis activities. Methods: This study is an experimental study using PANC-1 cells as objects. The phytochemical compounds were analyzed with LC-MS/MS. The cytotoxic activity of extracts and their combinations was determined using the MTT assay method in the PANC-1 cell line. Apoptosis, cell cycle arrest, and PI3K/mTOR profiles were analyzed with flow cytometry. Immunocytochemistry was used to determine Bcl-2, Cyclin D1, and p53 expression. Results: The phytochemicals found were five compounds with retention times of 8.96, 9.85, 10.52, 12.59, and 10.36. The results of the MTT assay showed that the IC50 values of extract and CIS were 21.83 ± 0.46 µg/mL and 3.02 ± 0.44 µg/mL, respectively. The combination index (CI) value of extract and CIS had a synergistic effect. Combination extract and CIS induced early and late apoptosis, inhibited cell cycle progression on the G1 phase, inhibited Bcl-2 and cyclin D1 expression, induced p53 expression, and inhibited PI3K and mTOR expression. Conclusions: The combination of extract and CIS showed anticancer activity against PANC-1 cells through induction of apoptosis and cell cycle arrest via inhibition of PI3K and mTOR expressions.